Lithium-induced Clock Gene Expression in Lymphoblastoid Cells of Bipolar Affective Patients - Kittel-Schneider, S.; Schreck, S.; Ziegler, C.; Weiflog, L.; Hilscher, M.; Schwarz, R.; Schnetzler, L.; Neuner, M.; Reif, A. (Pharmacopsychiatry, 2015)
Introduction: Disturbances of circadian rhythms occur in all episodes of bipolar disorder (BD). Lithium, as gold-standard in the maintenance treatment of BD, is known to influence circadian processes. Methods: In a pilot study lymphoblastoid cell lines (LCLs) were generated from 8 BD patients and 6 healthy controls. The LCLs were treated with lithiumchloride (LiCl) for 3 weeks. Cell cycles were then synchronized and expressional analysis by quantitative Real Time PCR was done. Results: BD and controls differed in the period length regarding DBP (albumin D-box binding protein) expression and DBP expression was also influenced by lithium treatment. Furthermore, baseline DBP expression was significantly different between non-treated BD and healthy controls. None of the other analyzed circadian genes showed to be influenced by chronic lithium treatment or to be differentially regulated due to the diagnosis. Discussion: We here show that chronic lithium treatment of LCLs leads to decreased expression of the clock gene DBP, rendering DBP a lithium-regulated gene. We could confirm the role of the circadian clock as well in lithium mode of action as in the pathomechanisms of BD although future studies with a greater number of participants and cell lines are needed.
CRIS-Team Scopus Importer:2026-04-08
Keywords: bipolar disorder; bipolar disorder treatment; circadian rhythm; clock genes; lithium